A Group of Novel HIF‐1α Inhibitors, Glyceollins, Blocks HIF‐1α Synthesis and Decreases Its Stability via Inhibition of the PI3K/AKT/mTOR Pathway and Hsp90 Binding. Issue 4 (April 2015) - Lee, Sun‐Hee; Jee, Jun‐Goo; Bae, Jong‐Sup; Liu, Kwang‐Hyoen; Lee, You Mie
<x xml:space="preserve">Abstract</x> Glyceollins, a group of phytoalexins isolated from soybean, are known to exhibit anticancer, antiestrogenic, and antiangiogenic activities. However, whether glyceollins regulate tumor growth through regulation of hypoxia‐inducible factor (HIF)‐1α has not been investigated. We determined whether and how glyceollins regulate the synthesis and stability of HIF‐1α. Quantitative real‐time PCR revealed that glyceollins inhibited the expression of HIF‐1‐induced genes such as vascular endothelial growth factor (VEGF) in cancer cells. Enzyme‐linked immunosorbent assay and reporter luciferase assay showed that glyceollins decreased VEGF secretion and its promoter activity, respectively. Treatment of various cancer cells with 0.5–100 µM glyceollins under hypoxic conditions reduced the expression of HIF‐1α. Glyceollins blocked translation of HIF‐1α by inhibiting the PI3K/AKT/mTOR pathway under hypoxic conditions. Glyceollins decreased the stability of HIF‐1α after treatment with cycloheximide, a protein synthesis inhibitor, and increased the ubiquitination of HIF‐1α after treatment with MG132, a proteasome inhibitor. Glyceollins blocked the interaction of Hsp90 with HIF‐1α, as shown by immunoprecipitation assay. Chemical binding of Hsp90 with glyceollins, as confirmed by computational docking analysis, was stronger than that with geldanamycin at the HSP90 ATP‐binding pocket. We found that glyceollins decreased microvessel density, as well as expression of phosphorylated AKT/mTOR and the Hsp90 client protein CDK4, in solid tumor tissues. Glyceollins potently inhibited HIF‐1α synthesis and decreased its stability by blocking the PI3K/AKT/mTOR pathway and HSP90 binding activity, respectively. These results may provide new perspectives into potential therapeutic application of glyceollins for the prevention and treatment of hypervascularized diseases and into the mechanism of their anticancer activity. J. Cell. Physiol. 230: 853–862, 2015. © 2014 Wiley Periodicals, Inc.